Purification, crystallization and initial X-ray diffraction study of human REV7 in complex with a REV3 fragment - Hara, Kodai (International Union of Crystallography, 2009)
REV7 is involved in various cellular functions including DNA replication, signal transduction and cell-cycle regulation. In DNA replication, REV7 interacts with REV3 and forms DNA polymerase ζ, which plays a central role in error-prone DNA synthesis. REV3 is a catalytic subunit and its activity is stimulated by REV7. To clarify the structural basis of the interaction between REV7 and REV3, human REV7 was crystallized in complex with a REV3 fragment. Two crystal forms were obtained. Crystal forms I and II belonged to space groups P2(1), with unit-cell parameters a = 43.8, b = 50.0, c = 107.3 Å, β = 96.9°, and P4(1)2(1)2 or P4(3)2(1)2, with unit-cell parameters a = b = 76.6, c = 118.4 Å, respectively.